A survey on Hadamard and Hilfer fractional differential equations: Analysis and stability. (September 2017) - Abbas, Saïd; Benchohra, Mouffak; Lazreg, Jamal-Eddine; Zhou, Yong
Abstract: In the present survey paper, we prove some results concerning the existence of solutions and weak solutions for some classes of Hadamard and Hilfer fractional differential equations. Some attractivity and Ulam stability results are presented. Our results are provided by applying the fixed point theory, and the technique of strong and weak measures of noncompactness.